Risk factors of obstructive sleep apnea syndrome in the developmental age - Sionek-Wręga, Irena; Jakubowska, Eliza; Hoppe-Mitera, Ewa; Ślemp, Julia; Pakuła, Anita; Kuźma, Krzysztof; Wręga, Jakub; Bierć, Karolina; Grochowska, Marcelina; Kisiel-Cybula, Ewelina (Quality in Sport, 2024)
Background: Obstructive Sleep Apnea Syndrome (OSAS) is a prevalent respiratory sleep disorder in children, associated with severe health consequences, including hypertension, cardiac dysfunction, and neurocognitive impairment. Despite extensive research on OSAS in adults, the risk factors for pediatric OSAS remain underexplored. Objective: This literature review aims to identify and present the key risk factors associated with pediatric OSAS based on contemporary studies. Methods: A systematic search of the PubMed and Scopus databases was conducted for literature published between 2016 and 2024. Search terms included “obstructive sleep apnea,” “children,” and “risk factors.” A total of 93 relevant studies were reviewed after excluding non-pediatric and irrelevant papers from an initial pool of 283. Results: The most commonly identified risk factors for pediatric OSAS include adenoid and tonsillar hypertrophy, obesity, craniofacial abnormalities, and asthma. Additional risk factors such as allergic rhinitis, recurrent upper respiratory infections, nasal stenosis, congenital diseases, low vitamin D levels, and preterm birth were also noted. Conclusion: Pediatric OSAS is influenced by multiple factors, including anatomical, physiological, and genetic components. Further research is required to explore emerging risk factors, such as role of vitamin D deficiency and microbiota, and to clarify the impact of variables like ethnicity and breastfeeding.